Citation Analysis Conducted On Doctoral Theses Of Science And Social Sciences In Reference To ICFAI University (Journal of Namibian Studies : History Politics Culture, 2023)
The study is based on the citation analysis of doctoral theses submitted to ICFAI University, Dehradun which was established under ICFAI University Act 2003. The main objective of this study is to determine the use of information sources by the research scholars of the University for completing their doctoral theses. There are a total of 23 numbers of doctoral theses awarded from the year 2012 to 2020.Among those theses thirteen theses are from social science departments and remaining ten theses belong to science departments. The study is conducted on the 8979 citations appended in these theses. Bibliographical entries illustrated at the end of the theses were collected and analyzed on several parameters like bibliographic form, authorship pattern, geographic distribution of citations, scattering of Indian and foreign author's citations and chronological distribution of citations. The image that will come out from this study would serve as a user study of library users hence it helps the librarians to enrich library collection as per the needs of the user demand for the learning resources and in designing of user services in libraries.